The Effect of Naloxone Access Laws on Fatal Synthetic Opioid Overdose Fatality Rates - Mohammad Tabatabai; Robert L. Cooper; Derek M. Wilus; Ryan D. Edgerton; Aramandla Ramesh; Samuel A. MacMaster; Parul N. Patel; Karan P. Singh (Journal of Primary Care & Community Health, 2023)
Background: Increases in fatal synthetic opioid overdoses over the past 8 years have left states scrambling for effective means to curtail these deaths. Many states have implemented policies and increased service capacity to address this rise. To better understand the effectiveness of policy level interventions we estimated the impact of the presence of naloxone access laws (NALs) on synthetic opioid fatalities at the state level. Methods: A multivariable longitudinal linear mixed model with a random intercept was used to determine the relationship between the presence of NALs and synthetic opioid overdose death rates, while controlling for, Good Samaritan laws, opioid prescription rate, and capacity for medication for opioid use disorder (MOUD), utilizing a quadratic time trajectory. Data for the study was collected from the National Vital Statistics System using multiple cause-of-death mortality files linked to drug overdose deaths. Results: The presence of an NAL had a significant (univariate P -value = .013; multivariable p-value = .010) negative relationship to fentanyl overdose death rates. Other significant controlling variables were quadratic time (univariate and multivariable P -value < .001), MOUD (univariate P -value < .001; multivariable P -value = .009), and Good Samaritan Law (univariate P -value = .033; multivariable P -value = .018). Conclusion: Naloxone standing orders are strongly related to fatal synthetic opioid overdose reduction. The effect of NALs, MOUD treatment capacity, and Good Samaritan laws all significantly influenced the synthetic opioid overdose death rate. The use of naloxone should be a central part of any state strategy to reduce overdose death rate.